Pengaruh Jumlah Sudu Terhadap Optimalisasi Kinerja Turbin Kinetik Roda Tunggal - Pietersz, Richard; Soenoko, Rudy; Wahyudi, Slamet (Jurnal Rekayasa Mesin, 2013)
Indonesia has a great potential to develop hydropower, because Indonesia's mountainous topography and hilly and is drained by numerous rivers (large and small), and in certain areas t here are lakes or reservoirs and the potential of water as an energy source. Hydroelectric Power Plant (PLTA) is a technology that has been proven to not harm the environment, support the diversification of energy as renewable energy, support the use of fuel reduction program, and most of the construction using local materials. Kinetic Turbine is one of the options in utilizing the potential of the kinetic energy in the form of velocity, kinetic studies using vertical shaft turbine, blade-shaped bowl that can withstand the flow in order to increase the tangential force generated. Amount of kinetic turbine blades is one of the variables that affect the rotation and tangential style of a turbine, so the effect on the value of the power and efficiency of a kinetic turbine. The results showed the influence of the number of blades on the power and efficiency of blade number 5, 7, 9 and 11,where the number of blades 11 have a greater influence than the number of blade 5, 7 and 9.Keywords: Water turbine, number of blades, performance